2009
DOI: 10.1007/s12263-009-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and brain health: multiple effects underpinned by common mechanisms

Abstract: The neuroprotective actions of dietary flavonoids involve a number of effects within the brain, including a potential to protect neurons against injury induced by neurotoxins, an ability to suppress neuroinflammation, and the potential to promote memory, learning and cognitive function. This multiplicity of effects appears to be underpinned by two processes. Firstly, they interact with important neuronal signalling cascades leading to an inhibition of apoptosis triggered by neurotoxic species and to a promotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
182
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 274 publications
(190 citation statements)
references
References 83 publications
(77 reference statements)
3
182
0
5
Order By: Relevance
“…It appears that these low-molecular-weight non-nutrient components are able to impact on memory through their ability to exert effects directly on the brain's innate architecture for memory (3,47,142,143) . The concentrations of flavonoids and their metabolites that reach the brain are thought to be sufficiently high to exert pharmacological activity at receptors, kinases and transcription factors.…”
Section: Modulation Of Synaptic Plasticity and Neuro-cognitive Performentioning
confidence: 99%
“…It appears that these low-molecular-weight non-nutrient components are able to impact on memory through their ability to exert effects directly on the brain's innate architecture for memory (3,47,142,143) . The concentrations of flavonoids and their metabolites that reach the brain are thought to be sufficiently high to exert pharmacological activity at receptors, kinases and transcription factors.…”
Section: Modulation Of Synaptic Plasticity and Neuro-cognitive Performentioning
confidence: 99%
“…It was also found that quercetin increases the activity of superoxide dismutase and reduces the malondialdehyde levels in the aging brain, thus indicating its role in decreasing oxidative stress with consequent improvements in cognition (Spencer, 2009). The quercetin supplementation reduced the loss of HuC/D neurons and enteric glial cells in the duodenum enteric plexus of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The most important group of polyphenols described for their advantageous benefits in promoting neuronal repairing and neuroplasticity are the flavonoids and curcuminoids. Flavonoids are found in many fruits and vegetables or their subproducts, such as berries [e.g., blueberries, strawberries], tea, and red wine [38]. For instance, the polyphenol resveratrol, a nonflavonoid polyphenol with 2 isomeric forms: the biologically inactive cis-resveratrol, and the biologically active transresveratrol [trans-3,4, 5-trihydroxystilbene], increases longevity while preserving memory and hippocampal microstructure.…”
Section: Dietary Polyphenolsmentioning
confidence: 99%